Activity Based Costing Approach for Determining Room Price in Hotel Borneo - B42112009, Annisa Yulianti Yulianti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Abstract : Activity Based Costing approach that present in the middle of the accountancy world is helps to reduce over-costing or under-costing that caused by charging distortion. Activity Based Costing approach can be used as a reference to the room price setting in the hotel and as a comparison with the prior room price, as well as being one of the inputs that provide information about Activity Based Costing approach. The purpose of this study was to analyze the difference between the prior room price with calculation of room price using Activity Based Costing approach. Research was arranged at the Hotel Borneo Pontianak. This approach are expected to supporting the management decision, both startegic and operational also increase the sales escalation. Keywords : Activity Based Costing, Room Price, Cost Driver